Form-Focused Instruction, Technology, and Limitations: An Investigation of Past Research and Future Possibilities - Schenck, Andrew (Frontiers in Psychology, 2022)
Modern studies that integrate technology with form-focused instruction (FFI) are useful, yet analysis of grammatical or learner differences is often limited. Without consistent examination of all factors that influence the efficacy of FFI, it is no surprise that results are often inconsistent. Recent synthesis of research concerning Korean, Persian, and Chinese learners suggests that grammatical difficulty (collectively defined by grammatical complexity, learner proficiency, and L1) determines when providing input is more effective, and when prompting a learner to produce output is more effective. Results suggest that input and explicit information may help learners produce language more accurately when grammatical difficulty is high (e.g., a grammatical feature is complex and learner proficiency is low). Conversely, compelling a learner to produce output appears to increase accuracy when difficulty of a grammatical feature is low (e.g., a grammatical feature is not complex and proficiency is high). More experimental research is needed to confirm results. Such research may provide a holistic perspective needed to tailor computer software to learner needs.